Answer:
Explanation:
To find the roots of the equation x^3 + 2x = x^2 + 2, we need to solve the equation for x. To do this, we can start by subtracting x^2 and 2 from both sides:
x^3 + 2x - x^2 - 2 = 0
This simplifies to x^3 - x^2 + 2x - 2 = 0. Next, we can factor the left side of the equation as follows:
(x - 2)(x^2 + 2x + 1) = 0
Since the product of two factors is equal to 0, this means that at least one of the factors must be equal to 0. Therefore, the roots of the equation are the solutions to the equations x - 2 = 0 and x^2 + 2x + 1 = 0. The first equation has a single solution at x = 2, and the second equation is a quadratic equation that can be solved using the quadratic formula:
x = (-2 +/- sqrt(4 - 411)) / (2*1)
= (-2 +/- sqrt(4 - 4)) / 2
= (-2 +/- sqrt(0)) / 2
= (-2 +/- 0) / 2
= -1 or -1
Therefore, the roots of the equation x^3 + 2x = x^2 + 2 are x = 2, x = -1, and x = -1.